Migrant Sex Workers and State Regulation in North Cyprus - Güven - Lisaniler, Fatma; Rodriguez, Leopoldo; Uğural, Sevin (Women's Studies International Forum / ELSEVIER, 2005)
North Cyprus is one of the destinations of women from Eastern Europe seeking economic opportunities abroad as sex workers. This paper, adopting a ‘labour’ approach to migrant sex work, focuses on working conditions in nightclubs and pubs. We examine the effects of laws governing immigration to North Cyprus and furnishing the regulatory framework for ‘entertainment’ establishments. Our research involved data from the relevant government offices; newspaper reports; and interviews with a member of the House of Representatives, a nightclub owner and a sample of 16 women working in the industry. Our principal finding is the contradiction of an official policy that on the one hand rules prostitution in nightclubs and pubs illegal while on the other submits the women in question to punitive regulations that implicitly acknowledge their engagement in sex work and enable tax revenue from their earnings, while failing to protect their interests and rights.
Keywords: Migrant Sex Workers - Cyprus, North